Preliminary results of propranolol treatment for patients with infantile hemangioma - Corapcioğlu, Funda; Büyükkapu-Bay, Sema; Binnetoğlu, Köksal; Babaoğlu, Abdulkadir; Anik, Yonca; Tugay, Melih (The Turkish Journal of Pediatrics, 2011)
Propranolol, a non-selective beta-blocker, has recently been introduced as a treatment for infantile hemangiomas. In this study, we evaluated the effect of propranolol in 12 infants with hemangioma. Twelve infants (9 girls) with a median age of 4.5 months were included in the study. All of the patients in the study group received short-term (1-9 weeks, median: 4 weeks) systemic corticosteroids as a first-line therapy. All patients received propranolol 2 mg/kg/day, divided into three doses. They were treated in an inpatient setting for the first 72 hours of the treatment. Vital signs, blood pressure and blood glucose were monitored. Propranolol treatment was given for 4-9 months (median: 5 months). In the study group, regression rate of the mean dimension of the lesion was 38% +/- 15 (range 15%-50, median 45%) at the 2nd month of therapy. Over 9 months, which was the maximum follow-up period, the regression rate of the mean dimension of the lesion was 55% +/- 31 (range 20%-80, median 50%). One patient had transient bradycardia, which improved spontaneously. No other side effect was observed in the study population. Propranolol appears to be an effective drug for infantile hemangiomas with good clinical tolerance. We suggest that propranolol is the preferable drug as the first-line therapy for infantile hemangiomas.